(3cTa GdHQGbY GdRgQjI Yf GdLQjOI GdHgjIs - (3YeQ GdWQGHjTis; (3GdOQOjQ , CMeO Hf eMeO Hf CMeO GdYOhj, CHh GdHQcGJ,J (B1201 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdePfH GdeLghd YeQ GdWQGHjTi GdePdhd deG QCjJ QSGdI GdTjN CMeO GdYOhiaTQMJgG TQMkG jHjf fhQ hLggG s
(3BNQgG (B:s
(3dXGgQ bhdg JYGdi hLhg jheFP fGVQI Edi s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B244 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B67s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds